Post-discharge follow-up of pediatric COVID-19 patients: insights into serological dynamics - Mahmoudi, Shima; Pourakbari, Babak; Shahbabaie, Mohammad Ali; Sotoudeh, Maryam; Jafari, Erfaneh; Hosseinpour Sadeghi, Reihaneh; Mamishi, Setareh (Frontiers in Microbiology, 2024)
Introduction: Limited data are available regarding SARS-CoV-2 serological response dynamics in pediatric patients with COVID-19, contributing to gaps in our understanding of the immune response in this population. This study aimed to investigate SARS-CoV-2 IgG seropositivity in patients diagnosed with COVID-19 during hospitalization and 2 to 4 weeks after discharge. Methods: A cohort of patients, consisting of 31 individuals with confirmed acute COVID-19 infection and 27 diagnosed with Multisystem Inflammatory Syndrome in Children (MIS-C), was enrolled in the study. Follow-up clinic appointments were scheduled for 2 to 4 weeks post discharge. During admission and follow-up, blood samples were collected from each patient for laboratory analysis. Anti-nucleoprotein SARS-CoV-2 IgG levels were determined using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results: At admission, 52% (n=14) of MIS-C patients and 10% (n=3) of acute COVID-19 patients had positive SARS-CoV-2 IgG test. Only 48 cases were referred to the hospital, and follow-up data was available for 20 cases with MIS-C and 28 cases with acute COVID-19. All patients (n=15) who initially tested positive for SARS-CoV-2 IgG at admission remained positive during follow-up (100%). Among the 33 patients who initially tested negative, 12 (37.5%) showed a positive result during follow-up, while 21 (62.5%) remained negative. Within this subgroup, 11 cases (44%) were diagnosed with acute COVID-19, and one patient (12.5%) presented with MIS-C. Fourteen cases with acute COVID-19 infection (56%) and seven cases with MIS-C (87.5%) consistently showed negative serology results throughout the study. During followup, the median lymphocyte count demonstrated a significant difference, with 0.96× 10⁹ cells per L (IQR: 0.75-3.0× 10⁹ cells per L) in the SARS-CoV-2 IgG-negative group and 2.9× 10⁹ cells per L (IQR= 1.33-7.22× 10⁹ cells per L) in the SARS-CoV-2 IgG-positive group (p-value= 0.03). Patients who demonstrated seropositivity during the follow-up were associated with a notably severe disease (p-value= 0.028). Our study highlights the dynamic nature of SARS-CoV-2 IgG antibody responses in pediatric patients with COVID-19. We observed a notable increase in seropositivity rates during follow-up. Furthermore, patients who were seropositive at follow-up demonstrated a severe disease course and lower lymphocyte counts compared to those with persistently negative serology.